Periodontal Splinting Choises For Patient With Edentulous - Adisty Restu Poetri; Helmi Fathurrahman; Anggun Amanda Saveria (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2021)
Background: Mobile tooth is a problem that often occurs and result in tooth loss. It caused by disease or periodontal tissue’s injury. Splint is a device that is made to stabilize or tighten mobile tooth due to a trauma or disease. It works by distribute the occlusion pressure to reduce tooth mobility. Removable partial denture frame is one treatment for missing teeth and permanent splints. Objective: The aim of this treatment is to explained effect of periodontal splints for edentulous patient. Case: First case: A woman complained mobile teeth on the incisors. Intraoral examination showed remaining teeth couldn’t be abutment. Second case: A woman complained mobile teeth on the incisors. Intraoral examination showed remaining teeth could be abutment. Case management: First case: Patient was given initial therapy and continued with rehabilitative therapy by removable partial denture metal frame. Second case: Patient was given initial therapy splinting using fiber reinforced composite. A week post treatment patient felt comfortable. Conclusion: It can be concluded periodontal splinting reduced teeth mobility and prevent further damage to the periodontal tissue og Edentulous patient.